ANALISA PERBEDAAN KINERJA KEUANGAN (ASSET MANAGEMENT RATIO) PADA PERUSAHAAN PARTISIPAN INDONESIA SUSTAINABILITY REPORT AWARDS (ISRA) 2009 â 2011 - Christy, Mellisa (Business Accounting Review, 2014)
Sustainability report becomes a trend that develops in the world of accounting that is a report informing about the performance of the economic, social, and environment for stakeholders. Because of this trend, thenÂ  an event held to give the award to the company that has published a sustainability report i.e. Indonesia Sustainability Report Awards.This research aimed to analyze the different financial performance of the asset management ratio on participants of ISRA 2009 â 2011. The sample of this research is 25 public companies that participated in ISRA 2009 â 2011. The independent variables in this research were categorized into three which were consistent or not in participating, business sectors, and the company size. Dependent variables in this research using the five ratio measurement of asset management ratio i.e. inventory turnover, receivable turnover, net working capital turnover, fixed asset turnover, and total asset turnover. The results showed that there was no difference in the financial performance of the asset management ratio on the participant of ISRA 2009 â 2011 from consistent or not in participating, business sectors, and the company size.